2018
DOI: 10.1063/1.5038600
|View full text |Cite
|
Sign up to set email alerts
|

Optimal dynamic induction control of a pair of inline wind turbines

Abstract: We study dynamic induction control for mitigating the wake losses of a pair of inline wind turbines. In order to explore control strategies that account for unsteady interactions with the flow, we employ optimal control and adjoint-based optimization in combination with large-eddy simulations. The turbines are represented with an actuator line model. We consider a simple uniform inflow case with two NREL 5 MW turbines spaced 5 diameters apart and find that optimal control leads to 25% gains compared to standar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 54 publications
4
27
0
Order By: Relevance
“…The wall shear stress is computed according to the standard log law 14,20 . In wake flow simulations, a fringe zone is used to adjust the flow from the downstream wake state to an undisturbed inflow condition [21][22][23] . The vertical profiles of mean wind speed and turbulence intensity in the streamwise direction obtained from the precursor simulation are shown in Fig.…”
Section: Large-eddy Simulation Frameworkmentioning
confidence: 99%
“…The wall shear stress is computed according to the standard log law 14,20 . In wake flow simulations, a fringe zone is used to adjust the flow from the downstream wake state to an undisturbed inflow condition [21][22][23] . The vertical profiles of mean wind speed and turbulence intensity in the streamwise direction obtained from the precursor simulation are shown in Fig.…”
Section: Large-eddy Simulation Frameworkmentioning
confidence: 99%
“…These findings have important implications for the design of advanced wind farm control algorithms that use blade pitch to regulate turbine axial induction (e.g. Yılmaz & Meyers 2018), which cannot expect the wake to react immediately to changes in blade pitch.
Figure 5.( a ) Sample change in blade pitch angle at a constant rate (dashed black line) and the resulting wake expansion response (solid red line).
…”
Section: Resultsmentioning
confidence: 98%
“…In addition to gaining insight into wake behaviours occurring during normal utility-scale wind turbine operation, improved understanding of the dynamic wake is crucial for the design of recently proposed advanced wind farm control algorithms, including thrust optimization (Goit & Meyers 2015; Munters & Meyers 2017; Shapiro et al. 2017; Munters & Meyers 2018 b ; Yılmaz & Meyers 2018), yaw angle modification (Gebraad, Fleming & van Wingerden 2015; Raach et al. 2017, 2018; Fleming et al.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such prediction from individual turbines can be further integrated into the turbine controllers to improve the control strategy of a wind farm for enhancing overall power production and/or mitigating structural damages, constituting the concept of "smart" wind farms in the future. Such concept has been demonstrated in some recent studies, including dynamic pitch variation used to move wake breakdown closer to the turbine [73,74], and yaw steering that deflects wakes away from downstream turbines to improve overall power production of a wind farm [65,75]. It is worth noting that although our study has revealed some statistical correlations between near-wake behavior and individual turbine parameters, the wake behavior in the field is influenced by multiple intertwining physical processes and cannot be readily predicted with a single turbine parameter.…”
Section: Conclusion and Discussionmentioning
confidence: 99%